Pengaruh Penerapan Zakat Perusahaan terhadap Kinerja Finansial: Studi Kasus pada Perusahaan Syariah di Indonesia: The Effect of Corporate Zakat Implementation on Financial Performance: Case Study of Sharia Companies in Indonesia - , Ahmad Nurrohim; Ijai Varol Abiansyah; Aura Azhara; Agustin , Ayu; Al Ghifari , Irsyad; Firdaus Fathan, Gifari; Farhana, Nadia (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2024)
Zakat will provide benefits for both the giver and the recipient because it can be an added value that increases the reputation which will certainly affect the growth of company performance or company profitability. The method used in this research is literature study to analyse the effect of corporate zakat implementation on financial performance of Islamic companies in Indonesia. Literature study was chosen because of the collection and analysis of relevant data from various existing scientific sources, so as to provide a deeper understanding of the topic under study. The results showed that the application of corporate zakat in Indonesia, especially in the field of Islamic companies is important to understand how zakat can affect the financial performance of Islamic companies in Indonesia. The first study on the application of zakat in Islamic companies in Indonesia shows that zakat has no effect on corporate reputation, while CSR is proven to improve reputation which indicates that although zakat has the potential to improve financial performance, Islamic banks in Indonesia have not been optimal in distributing zakat. Meanwhile, in the second study conducted at PT Bank Muamalat Indonesia Tbk for the period 2012-2020, where the results showed that zakat did not have a significant effect directly on financial performance, but the existence of zakat in the social and economic context remains important. Therefore, Islamic companies in Indonesia, especially banks, need to further explore the potential of zakat and optimise it within the framework of CSR. Awareness of the importance of zakat and CSR can be a key factor in encouraging sustainable economic growth and improving people's welfare in Indonesia.